GEOGRAFIC INDICATIONS OF ORIGIN OF AGRICULTURAL AND FOOD PRODUCTS - Savić, Mirjana; Đurić, Ivan (Economics of Agriculture, 2008)
Agricultural producers have interest for their products to be more competitive on both, domestic and international market. They can achieve this if they have high quality products, which have specific, well recognized characteristics. Those products are with specific geographical characteristics. Those products have significantly bigger market price and value. Large number of European countries is involved in creation of preconditions for achieving the sign of protected designation of origin (PDO) for their products. In Serbia, large numbers of high quality products, which have all necessary characteristics to get the PDO sign, are not registered, and they are not protected. There is a low regulative concerning PDO product in Serbia and it also refers to low protection of intellectual rights concerning inventions, trademarks, authorized work, design, and PDO. Products from Serbia should be protected by the low regulative before and then if they satisfy the conditions of EU directives 510/06, then they can be exported to the EU.